PENGARUH CITRA MEREK DAN KESADARAN MEREK TERHADAP EKUITAS MEREK HANDPHONE SAMSUNG BERSISTEM ANDROID (Studi di Kota Semarang) - Ginar Gumelang, 09.05.51.0009; Yulianto, Heru (Students Journal of Economic and Management, 2013)
The research is based on the phenomenon of competition among various companies manufacturing android-based smartphone. The increase of Samsungâs android-based smartphone sales numbers in 2011-2012 indicates the rise of brand equity on Samsung phones. It is supposed that brand image and brand awareness may influence the establishment of a strong brand equity. Therefore, this research aims to analyze the effect of brand image and brand awareness on the brand equity of Samsungâs android-based smartphone in Semarang. Using purposive sampling and accidental sampling, the research takes samples of 100 respondent who has used or are using android smartphones from Samsung. A data analysis is then done on primary data obtained quantitatively, qualitatively, and descriptively. Quantitative analysis includes: validity, reliability testing, multiple linear regression analysis, F test, t test, and analysis of the coefficient of determination R2. The results showed the brand image (X1) and brand awareness (X2) proved to be positively and significantly affect brand equity (Y). Brand equity is dominated by the formation of brand awareness followed by brand image.Key words: Brand Image, Brand Awareness and Brand Equity.